Options for operation and maintenance partnerships - a case study of Rupike Irrigation Scheme, Zimbabwe - Mwendera, Emmanuel; Chilonda, Pius; Chigura, Patrick (2013)
Adequate operation and maintenance (O&M) of irrigation infrastructure sustains irrigation scheme facilities, reduces repair costs, helps the system last longer, and keeps irrigation efficiency at design levels. In cases where farmers do not have sufficient capacity to operate and maintain the irrigation infrastructure sustainably, it is necessary for the farmers to enter into partnerships with external entities. The paper presents assessment of partnerships required for small-scale farmers at Rupike Irrigation scheme, in Masvingo, Zimbabwe, to operate and maintain their irrigation infrastructure sustainably. The O&M domain in the irrigation scheme consisted of five components of water acquisition (WA), water transmission (WT), water pumping (WP), water distribution (WD) and field water application (WAP). Group discussions of the farmers were held to obtain farmers’ input in the identification of components and activities for which partnerships were required. It was proposed that the scheme requires public-community partnership (PUCP) to operate and maintain the dam, public-private-community partnership (PUPVTCP) to operate and maintain the pump house, private-community partnership (PVTCP) to operate and maintain the transmission and mainline and field distribution pipelines, and public-community partnership (PUCP) to operate and maintain field application and crop production systems. It was also proposed that each partnership be formalised through contractual arrangements. It was recommended that the farmers improve funding for O&M through increased contributions as well as through partnerships with the private sector. It was also recommended that, for effective partnerships in irrigation schemes, it is important to analyse the scheme components and identify where and how such partnerships are needed for sustainable O&M of scheme infrastructure.